2021
DOI: 10.1007/s10555-021-10012-4
|View full text |Cite
|
Sign up to set email alerts
|

Progression and metastasis of small cell lung carcinoma: the role of the PI3K/Akt/mTOR pathway and metabolic alterations

Abstract: Small cell lung carcinoma (SCLC) is characterized by high metastatic rate and poor prognosis. The platinum-based chemotherapy still represents the backbone of the therapy; however, acquired resistance develops almost in all patients. Although SCLC has been formerly considered a homogeneous disease, recent advances in SCLC research have highlighted the importance of inter- and intratumoral heterogeneity and have resulted in the subclassification of SCLC. The newly described SCLC subtypes are characterized by di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 141 publications
0
20
0
Order By: Relevance
“…mTOR pathway plays a critical role in tumorigenesis and cancer progression [ 12 ], and a potential correlation has been identified between MYBL2 and mTOR in Arabidopsis [ 13 ]. In order to explore whether MALAT1 and MYBL2 are related to the mTOR pathway in PCa, we utilized mTOR pathway inhibitor rapamycin and found that it reduced the growth rate (Figures 3(a) and S1G ) and the number of colonies of PCa cell lines significantly (Figures 3(b) and S1H ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…mTOR pathway plays a critical role in tumorigenesis and cancer progression [ 12 ], and a potential correlation has been identified between MYBL2 and mTOR in Arabidopsis [ 13 ]. In order to explore whether MALAT1 and MYBL2 are related to the mTOR pathway in PCa, we utilized mTOR pathway inhibitor rapamycin and found that it reduced the growth rate (Figures 3(a) and S1G ) and the number of colonies of PCa cell lines significantly (Figures 3(b) and S1H ).…”
Section: Resultsmentioning
confidence: 99%
“…Since MYBL2 is a potentially carcinogenic gene, its role in tumorigenesis and progression, as well as the mechanisms and downstream signaling pathways, has been under intensive investigation. Interestingly, the classical mTOR signaling pathway controls tumorigenesis and progression [ 12 ], and a potential correlation between MYBL2 and mTOR has been detected in Arabidopsis [ 13 ] via the GSK3b pathway. Although this relationship between MYBL2 and mTOR pathway has only been verified in plants, a possibility of potential correlation between them in mammals should not be ignored.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the PI3K/AKT/mTOR signaling pathway serves a crucial role in the regulation of tumor growth, apoptosis, metabolism, invasion and metastasis, as well as angiogenesis (36)(37)(38). Therefore, the regulation of this pathway has become of interest in the treatment of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Ras can promote glucose uptake by upregulating the expression of GLUT1 on the cell membrane surface, which in turn increases aerobic glycolysis efficiency ( Healy et al, 2021 ). In addition, PI3K-Akt-mTOR signaling is also a significant regulator of glucose uptake, promoting GLUT1 expression and protein translocation from the inner membrane to the cell surface ( Krencz et al, 2021 ; Sanaei et al, 2021 ). P53 is the most critical oncogene, affecting the cell cycle by encoding transcription factors ( Liu et al, 2019 ; Alvarado-Ortiz et al, 2020 ).…”
Section: Tumor Aerobic Glycolytic Signaling Pathwaymentioning
confidence: 99%